Bioelastic properties of the aorta in children, adolescents and young adults after cardiac transplantation: a cardiovascular magnetic resonance study. (14th October 2021) - Mueller, F; Gummel, K; Reich, B; Latus, H; Jux, C; Voges, I
Abstract: Background: Long-term complications after cardiac transplantation are common and typically include arterial hypertension and coronary allograft vasculopathy. Few studies also suggested that heart transplant recipients have an increased arterial stiffness. Purpose: This prospective study aimed to assess the bioelastic properties of the aorta as well as LV function, morphology and structure in children and young adults after cardiac transplantation. Methods: CMR studies from 34 patients (median age: 17.1 years, range: 8–24 years) who underwent cardiac transplantation in childhood were analysed. Aortic anatomy and distensibility were assessed at five locations of the thoracic aorta using steady-state free precession cine sequences. Pulse wave velocity (PWV) of the aortic arch and the descending thoracic aorta was measured from 2-dimensional phase contrast images. Size and function of the left atrium and the ventricles were assessed from a stack of short axis slices. Myocardial T1 times were determined using a standard MOLLI sequence. Results: Cross-sectional areas of the ascending aorta and the aortic arch tended to be lower in patients compared to controls (ascending aorta 464.5±172.5 mm 2 vs. 515.3±186.3 mm 2, aortic arch 342.4±113.3 mm 2 vs. 376.9±148.5 mm 2 ) whereas cross-sectional areas of the descending aorta tended to be higher (aortic isthmus 283.7±102.1 mm 2 vs. 257.9±89.5 mm 2, aorta descendens diaphragmal 218.4±75.8 mm 2 vs. 214.2±75.0 mm 2 ) and showed a correlation with systolic blood pressure (r=0.33). PWV was higher in the aortic arch (4.8±2.4 m/s vs. 3.6±0.7 m/s). Aortic distensibility was slightly higher at all measuring points in the study population compared to the control group and showed an increase with rising distance from the heart (ascending aorta 10.5±5.8 10–3 mm Hg-1, aortic isthmus 13.1±7.5 10–3 mm Hg-1, descending aorta 16.6±6.8 10–3 mm Hg-1). Biventricular volumes were slightly reduced in the patient group compared to the control group but this was not statistically significant. Only left ventricular mass messured during the systolic phase was higher in the study population compared to the control group (males 55.1 g/m 2 vs. 53.0 g/m 2, females 46.2 g/m 2 vs. 45.2 g/m 2 ). T1 mapping demonstrated increased T1 times in the heart-transplanted group compared to published data in healthy adults. In particular, T1 times of the lateral and inferior myocardial segments were higher. Conclusion: Patients who underwent cardiac transplantation in childhood seem to have a reduced bioelasticity of the thoracic aorta. Increased myocardial T1 times suggesting alterations in myocardial structure. Funding Acknowledgement: Type of funding sources: None.